Work-related Experiences and Challenges of Perioperative Nurses in Southwestern Nigeria - Oyediran, Olufemi Oyebanji; Ayandiran, Emmanuel Olufemi; Ishola, Kofoworola Ebunoluwa; Fajemilehin, Boluwaji Reuben (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2024)
Background: Perioperative nursing is highly demanding due to the long hours of complex procedures, limited support, inadequate facilities, and staffing issues. These factors contribute to fatigue, frustration, and burnout. However, there is a paucity of data on the challenges and experiences of perioperative nurses in Southwestern Nigeria.Purpose: This study aimed to explore work-related experiences and challenges of perioperative nurses in selected hospitals in a southwestern state, Nigeria.Methods: The study adopted a phenomenological qualitative design. Twenty perioperative nurses who had spent a minimum of six months in the operating theatres of three public hospitals were selected. Data were collected through semi-structured interviews using a key informant interview guide. The qualitative data collected were transcribed verbatim, coded, and analysed using content and thematic analysis.Results: Findings from the study revealed two major themes: the experiences of perioperative nurses in Osun State and the challenges confronting perioperative nursing practice and perioperative nurses. The study reported perioperative nurses’ personal experiences, motivational factors, and their aspirations. Findings further showed that challenges to perioperative nursing include inadequate infrastructure and equipment, a shortage of manpower, financial constraints faced by patients, and insufficient funding for perioperative nursing services.Conclusion: The study concluded that perioperative nurses’ experiences were educative and fulfilling yet challenging and frustrating due to the numerous obstacles they face in their professional roles. Therefore, stakeholders need to address these challenges to enable perioperative nurses to function optimally and improve outcomes for surgical patients.